Scaling and Optimizing Consumer Tech Products with Multi-Armed Bandit Algorithms: Applications in eCommerce - Siddharth Gupta (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the application of Multi-Armed Bandit (MAB) algorithms in optimizing consumer tech products, with a particular focus on eCommerce platforms. It provides a comprehensive article overview of the theoretical framework behind MAB algorithms, including the exploration-exploitation trade-off and comparisons with traditional A/B testing methods. The article delves into various MAB strategies commonly used in eCommerce, such as epsilon-greedy, Upper Confidence Bound (UCB), and Thompson Sampling, and examines their applications in personalized product recommendations, dynamic pricing, ad placement optimization, and website content delivery. Implementation considerations, including integration with existing machine learning infrastructure and data processing in high-throughput scenarios, are discussed in detail. The article also addresses the impact of MAB algorithms on key performance metrics like user engagement, conversion rates, and revenue optimization. Ethical considerations, including transparency in automated decision-making and fairness in consumer-facing applications, are explored. Finally, the article presents case studies of successful implementations, discusses current challenges and limitations, and outlines future directions for MAB algorithms in eCommerce and potential cross-industry applications.